2017
DOI: 10.2298/psi1703383b
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural comparison for preference for symmetry: Comparing British and Egyptians non-experts

Abstract: The aesthetic appeal of symmetry has been noted and discussed by artists, historians and scientists. To what extent this appeal is universal is a difficult question to answer. From a theoretical perspective, cross-cultural comparisons are important, because similarities would support the universality of the response to symmetry. Some pioneering work has focussed on comparisons between Britain and Egypt (Soueif & Eysenck, 1971, 1972), including both experts and naive subjects. These studies confirmed some degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Classic Islamic art has a greater emphasis on abstract geometry (Gonzalez, 2001), whereas classic Western art celebrates beauty in human faces and bodies. However, Soueif and Eysenck (1971) studied preferences for shape and found similar results in Britain and Egypt and this has been confirmed recently (Bode, Helmy, & Bertamini, 2017). Although analysis of just two populations will never be sufficient to support claims of universality, it does at least go some way to addressing the generalisability of our results.…”
Section: Scientific Aestheticssupporting
confidence: 73%
“…Classic Islamic art has a greater emphasis on abstract geometry (Gonzalez, 2001), whereas classic Western art celebrates beauty in human faces and bodies. However, Soueif and Eysenck (1971) studied preferences for shape and found similar results in Britain and Egypt and this has been confirmed recently (Bode, Helmy, & Bertamini, 2017). Although analysis of just two populations will never be sufficient to support claims of universality, it does at least go some way to addressing the generalisability of our results.…”
Section: Scientific Aestheticssupporting
confidence: 73%
“…However, the orientation of the mirror symmetry axis impacts the speed and ease of detection. While prior research has shown conflicting findings, the literature suggests that the axis orientation from the easiest to the most difficult ones to detect are as follows: vertical axis > horizontal axis > diagonal axis > other oblique axes (Bode et al, 2017;Pecchinenda et al, 2014;Wagemans, 1997). It must be noted that perfect mirror symmetry is rare in real worldyet, the process of symmetry detection in humans is incredibly robust and noise-resistant (Treder, 2010;Wagemans, 1997).…”
Section: Consumer Liking and Symmetrymentioning
confidence: 99%
“…Preference for symmetry is inherent and strong (Creusen et al, 2010;Tinio and Leder, 2009), and holds for both actual objects and abstract stimuli (Shepherd and Bar, 2011). Symmetry in images should positively affect viewers' preference, pleasure, or liking (Bode et al, 2017;Reber et al, 2004a;Redies et al, 2020). In marketing, mirror symmetry in brand logos has been shown to positively influence consumer liking and interest (Henderson and Cote, 1998;van der Lans et al, 2009).…”
Section: Consumer Liking and Symmetrymentioning
confidence: 99%
“…Scientists and artists have claimed that symmetry is a fundamental and universal principle of esthetics, to which the human brain is particularly sensitive (for a review, see Bode et al, 2017). To measure symmetry, we used filter responses from the first layer of a convolutional neural network (CNN) that closely match responses of neurons in the visual cortex of higher mammals (Brachmann and Redies, 2016).…”
Section: Symmetrymentioning
confidence: 99%